Advantages of long- and short-reads sequencing for the hybrid investigation of the Mycobacterium tuberculosis genome - Di Marco, Federico; Spitaleri, Andrea; Battaglia, Simone; Batignani, Virginia; Cabibbe, Andrea Maurizio; Cirillo, Daniela Maria (Frontiers in Microbiology, 2023)
In the fight to limit the global spread of antibiotic resistance, computational challenges associated with sequencing technology can impact the accuracy of downstream analysis, including drug resistance identification, transmission, and genome resolution. About 10% of Mycobacterium tuberculosis (MTB) genome is constituted by the PE/PPE family, a GC-rich repetitive genome region. Although sequencing using short read technology is widely used, it is well recognized its limit in the PE/PPE regions due to the unambiguously mapping process onto the reference genome. In this study we exploited the third-generation sequencing technology such as Oxford Nanopore Technology (ONT) to extensively analyse MTB clinical strains. The aim of this study was to compare the performances of short-reads (SRS), long-reads (LRS) and hybrid-reads (HYBR) based analysis over different common investigative tasks. We observed the utility of LRS in offering a more comprehensive understanding of the PE/PPE family with respect to SRS in agreement with previous study. In addition to that, our analysis of the genome coverage highlights that PE and PPE genes can be included with acceptable results for unambiguous mapping, limiting the exclusion of PE_PGRS genes only. The LRS sequencing suffered the presence of issues in terms of signal-noise ratio but still can correctly identify genetically closed strains and drug resistance-associated mutations by increasing sequencing depth. The HYBR pipeline achieved synergic results in all the compared tasks exploiting the features of the two technologies without any critical drawback. In conclusion, depending on the aim of the investigation, both SRS and LRS present complementary advantages and limitations implying that for a full resolution of MTB genomes, where all the mentioned analyses and both technologies are needed, the use of the HYBR approach represents a valid option and a well-rounded strategy.